The Effect of Progressive Lateral Column Lengthening in a Novel Stage II-B Flatfoot Cadaveric Model Evaluated Using Software-Guided Radiographic Measurements of Foot Alignment. (August 2022) - Femino, John E.; Kern, Andrew; Schumer, Ross; Anthony, Christopher; Kruse, Adam J.; Goetz, Jessica
Background: This work used software-guided radiographic measurement to assess the effects of progressive lateral column lengthening (LCL) on restoring alignment in a novel cadaveric model of stage II-B flatfoot deformity. Methods: A stage II-B flatfoot was created in 8 cadaveric specimens by transecting the spring ligament complex, anterior deltoid, and interosseous talocalcaneal and cervical ligaments. Weightbearing computed tomographic (WBCT) scans were performed with specimens under 450 N of compressive load in the intact, flat, and 6-, 8-, and 10-mm lateral column–lengthening conditions. Custom software-guided radiographic measurements of the lateral talo–first metatarsal (Meary) angle, anteroposterior talo–first metatarsal angle, naviculocuneiform overlap, and 2 new measures (plantar fascia [PF] distance and angle) were recorded on digitally reconstructed radiographs. Four anonymized analysts performed measurements twice. Intra- and interobserver agreement was assessed using intraclass correlation coefficients (ICCs). Results: Six-millimeter LCL restored alignment closest to the intact foot in this new cadaveric model, whereas 10-mm lengthening tended toward overcorrection. The PF line displaced laterally in the flatfoot condition, and LCL restored the PF line to a location beneath the talonavicular joint. Interobserver agreement was excellent for PF distance (ICC = 0.99) and naviculocuboid overlap (ICC = 0.91), good for Meary angle (ICC = 0.81) and PF angle (ICC = 0.69), and acceptable for the talonavicular coverage angle (ICC = 0.65). Conclusion: In this stage II-B cadaveric flatfoot model, cervical ligament transection was essential to create deformity after the medial hindfoot ligaments were transected. Software-guided radiographic measurement proved reliable; standardized implementation should improve comparability between studies of flatfoot deformity. The novel PF distance performed most consistently (ICC = 0.99) and warrants further study. With this model, we found that a 6-mm LCL restored alignment closest to the intact foot, whereas 10-mm lengthening tended toward overcorrection. Clinical Relevance: Future joint-sparing flatfoot corrections may consider using a relatively small LCL combined with other bony and/or anatomic ligament/tendon reconstructions.